2010
DOI: 10.1007/s10152-010-0219-y
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of the peracarid crustaceans associated with the alga Corallina elongata along the intertidal rocky shores of the Iberian Peninsula

Abstract: Spatial patterns of intertidal peracarids, associated with the alga Corallina elongata, were studied along the whole Iberian Peninsula. A total of 28,215 specimens were collected, comprising 78 different species (57 amphipods, 16 isopods, 4 tanaids and 1 cumacean), most of them with Atlantic-Mediterranean distribution (60%) and only 9% of Mediterranean endemics. Gammarids were dominant in abundance and number of species, representing more than 70% of the total peracarids. The most common species collected duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 58 publications
(65 reference statements)
2
33
1
Order By: Relevance
“…There is one recent record for north-eastern England, which may be the result of a stranding, as are records for The Netherlands, where it is not considered indigenous (Holthuis 1956). The closest record to the Mediterranean of Dynamene bidentata is Tarifa, in southern Spain (Guerra-García et al 2011, Izquierdo and Guerra-García 2011, Guerra-García et al 2012, Torrecilla-Roca and Guerra-García 2012). …”
Section: Resultsmentioning
confidence: 99%
“…There is one recent record for north-eastern England, which may be the result of a stranding, as are records for The Netherlands, where it is not considered indigenous (Holthuis 1956). The closest record to the Mediterranean of Dynamene bidentata is Tarifa, in southern Spain (Guerra-García et al 2011, Izquierdo and Guerra-García 2011, Guerra-García et al 2012, Torrecilla-Roca and Guerra-García 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Given the cosmopolitan distribution of J. slatteryi, its presence in the Mediterranean has probably been underestimated due to a mixture of Jassa individuals being attributed to a single species of for example J. marmorata or J. cadetta (Navarro-Barranco, 2015). Separately, S. tergestina, although it has not been reported previously in fouling habitats, is common in natural habitats such as algae (Vazquez-Luis et al, 2008;Izquierdo & Guerra-García, 2011), mussels (Kalkan et al, 2006), soft-bottoms (Sezgin et al, 2007;FernandezGonzalez et al, 2016) or bryozoans (Conradi et al, 1997;Conradi & Lopez-Gonzalez, 1999), which may be present as biogenic habitats within the fish-farm fouling (Fitridge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pereira et al (2006) reported clear geographic differences, with a sharp gradient from north to south, in patterns of distribution of epifaunal crustacean species associated with dominant macroalgal species along the Portuguese rocky coast. Such a gradient could be driven by a combination of physical and biological factors, including the availability of seston and grain-size of sands (Sparla et al 1992), rafting of juveniles and adults (Guerra-García et al 2009;Izquierdo and Guerra-García 2010), temperature, water currents, and wave exposure (Pereira et al 2006), which are known to play a key role in driving the distribution of plant-associated epifaunal amphipods over large oceanic distances. It is worth mentioning that the herein amphipod records belong exclusively to the biogeographic AtlanticMediterranean category, and no subtropical or boreal Atlantic species were collected.…”
Section: Discussionmentioning
confidence: 99%